A survey on the implementation of health education among nurses in the stomatology clinic in Guangdong Province (广东省口腔门诊护士健康教育实施现状的调查研究) - SHEN Fang (沈芳); YE Ziwen (叶子文); FENG Xiaowen (冯晓文); SU Wanying (苏婉莹); XIAO Wei (肖炜) (中西医结合护理)
Objective To investigate the status quo of health education implemented by nurses in stomatology clinics in Guangdong Province, analyze the factors affecting the implementation of oral health education, so as to provide reference for the implementation of health education for patients in stomatology clinics in the future. Methods A self-designed questionnaire on the implementation of health education was used to investigate 382 oral outpatient nurses in Guangdong Province from May to July 2022 by convenience sampling method. Results Totally 344 valid questionnaires were obtained, the effective recovery rate was 90. 05%. Among the 344 nurses surveyed, 87. 79%(302/344)of them conducted health education assessment before health education, 56. 10%(193/344) of nurses made oral health education plan, and 63. 95%(220/344)of nurses conducted oral health education effect evaluation. Among the 344 nurses surveyed, 85. 47%(294/344)of the nurses in the dental clinic chose armchair preaching in the course of practice, 97. 97%(337/344)of the nurses said that "oral immediate preaching" was the main teaching medium. Information provided to patients mainly focuses on disease prevention, treatment, oral health care knowledge, etc. Among the 344 nurses surveyed, 86. 92%(299/344)nurses believed that the lack of manpower and full-time health education personnel were the main factors affecting the implementation of oral health education. Conclusion At present, there has been a lack of choice of health education methods and media. The theory of health education and oral professional knowledge need to be strengthened, the procedure and system of oral health education need to be standardized, and there is an urgent need to establish the full-time oral health education post. (目的 调查广东省口腔门诊护士实施健康教育的现状, 分析影响口腔健康教育实施的因素, 为未来口腔门诊患者健康教育的实施提供参考依据。方法 采用便利抽样的方法, 自行设计口腔门诊护士健康教育实施情况的调查问卷, 于2022年5—7月对广东省382名口腔门诊护士进行调查。结果 本次调查获得有效问卷344份, 有效回收率为90. 05%。在调查的344名护理人员中, 87. 79%(302/344)的护理人员在进行健康宣教前会进行健康教育评估, 56. 10%(193/344)的护士制定过口腔健康宣教计划, 63. 95%(220/344)的护士进行过口腔健康教育效果评价。85. 47%(294/344)的口腔门诊护士在实践过程中选择椅旁宣教, 97. 97%(337/344)的护士表示“口头即时宣教”为主要宣教媒介。为患者提供的信息主要集中在疾病的预防、治疗、口腔卫生保健知识等。86. 92%(299/344)的护理人员认为人力不足, 缺乏专职健康教育人员是影响护理人员实施口腔健康宣教的主要因素。结论 目前口腔门诊护理人员健康宣教方式和媒介选择单一, 健康教育理论、口腔专业知识亟待加强培训, 口腔健康教育的程序及体系有待规范, 口腔专职健康宣教岗位设置迫在眉睫。)